One year outcome of Subacromial Methylprednisolone Injection and Psychotherapy for Subacromial Impingement Syndrome - Lakhey, S; Manandhar, RR (Nepal Orthopaedic Association Journal, 2013)
BACKGROUND: Subacromial impingement syndrome is a common cause of pain in the shoulder region. When analgesics and physiotherapy are not helpful in relieving the patient’s shoulder pain, subacromial methylprednisolone injection is given. The aim of this prospective study was to determine the one year clinical outcome of subacromial injections of methylprednisolone and physiotherapy in patients with subacromial impingement syndrome. METHODS: The pain of thirty shoulders in twenty nine patients characteristic of subacromial impingement syndrome was assessed by Visual Analogue Scale (VAS) scores of 0 to 10, and the overall clinical and functional assessment was done by Constant Murley score. Each shoulder received methylprednisolone injection in the sub-acromial space by the posterior approach. The subacromial injections were repeated at two to three weekly intervals (a maximum of three injections) until the pain subsided to 2 or less in the VAS. This was followed by physiotherapy exercises. Treatment Outcome at final follow-up of one year was measured using VAS and Constant Murley Score. RESULTS: Pain before starting the injections was a mean of 7.87 in the VAS (range: 5-10 ). At the end of follow-up, it was a mean of 1.27 (range: 0 to 5). The Constant Murley Score was a mean of 30.83 (range: 6-49) before the start of injections. At the end of follow-up, it was a mean of 84.87(range: 70-96). CONCLUSION: Subacromial methylprednisolone injections followed by physiotherapy exercises can provide statistically and clinically satisfactory pain relief and improvement of shoulder function at one year follow up in 96.7% patients with subacromial impingement syndrome. DOI: http://dx.doi.org/10.3126/noaj.v1i1.8128 Nepal Orthopaedic Association Journal Vol.1(1) 2010